Spectroscopic profiling (FT-IR, FT-Raman, NMR and UV-Vis), autoxidation mechanism (H-BDE) and molecular docking investigation of 3-(4-chlorophenyl)-N, N-dimethyl-3-pyridin-2-ylpropan-1-amine by DFT/TD-DFT and molecular dynamics: A potential SSRI drug. (December 2018) - Abraham, Christina Susan; Muthu, S.; Prasana, Johanan Christian; Armaković, Sanja J.; Armaković, Stevan; Rizwana B., Fathima; A.S., Ben Geoffrey
Graphical abstract: Spectroscopic profiling in terms of FT-IR, FT-Raman, UV–vis and NMR in addition to reactivity study by density functional theory (DFT) and molecular dynamics (MD) simulations of 3-(4-chlorophenyl)-N, N-dimethyl-3-pyridin-2-ylpropan-1-amine (C16 H19 ClN2 ) have been discussed. The global quantum-molecular descriptor FMOs, NBO, NHO and NTO analysis are done. Local reactivity properties MEP, ALIE surfaces and Fukui functions, H-BDE and ELF were studied. Molecular docking study was executed to evaluate the potential of the title molecule to bind with 5-HT1 A serotonin receptor and thus can be a lead compound for developing new Selective serotonin reuptake inhibitor drug. By QSAR modeling the comparison of physiochemical parameters of commercially available SSRI drugs and title molecule is carried out. Highlights: The spectroscopic profiling (FT-IR, FT-Raman, UV–vis and NMR), PED and vibrational assignments are studied. Molecular dynamic simulation to determine MEP, ALIE, RDF and excitations Chemical bonding analysis (ELF), NBO and NHO analysis. Drug likeness, molecular docking and QSAR modelling: potential SSRI drug. Abstract: Spectroscopic profiling in terms of FT-IR, FT-Raman, UV–vis and NMR in addition to reactivity study by density functional theory (DFT) and molecular dynamics (MD) simulations of 3-(4-chlorophenyl)-N, N-dimethyl-3-pyridin-2-ylpropan-1-amine (C16 H19 ClN2 ) have been discussed. In order to assign principal vibrational numbers, the Potential energy distribution (PED) analysis has been executed. Frontier molecular orbitals (FMOs) analysis in addition to the stabilization energy and natural hybrid orbital analysis has been done. Local reactivity properties of this compound have been addressed through molecular electrostatic potential (MEP) and average local ionization energy (ALIE) surfaces. The bond dissociation energy for hydrogen abstraction (H-BDE) and chemical bonding analysis in terms of electron localization function gave details regarding the Pauli exchange repulsion effect in the electrons of the molecule. Molecular dynamics simulation has been performed in order to understand reactivity of title molecule with water. Molecular docking study was executed to evaluate the potential of the title molecule to bind with 5-HT1 A serotonin receptor and thus can be a lead compound for developing new SSRI (Selective serotonin reuptake inhibitor) drug. Aside from molecular docking, drug likeness parameters have been also considered and by QSAR modeling the comparison of physiochemical parameters of commercially available SSRI drugs and title molecule is carried out.